Strategy For Achieving SDGs Targets In Bone Bolango Regency Through The SWOT Approach - Yuniarti Koniyo; Juliana Juliana; Muchtar Ahmad (FKIP, Universitas Palangka Raya, 2024)
Bone Bolango Regency is part of the Tomini Bay area which is included in the sustainable development targets based on the SDGs achievement targets. This research aims to determine the strategy for achieving SDGs which will be used as the basis for economic development in Bone Bolango Regency. The research is qualitative research that uses respondents from related agencies who are determined based on purposive sampling. There were 5 respondents who were willing and were representatives of related agencies in Bone Bolango Regency. Data analysis uses SWOT analysis based on data obtained through questionnaires. The research results show that regulatory support (0.432) and priority of the Regional Medium Term Development Plan (0.359) are strength factors, while the weakness factor is institutional support (0.120). The opportunity factor is budget support (.045), while the threat factor is partnership support (0.043), which is still very limited. The SWOT factors found in Bone Bolango district are the basis used to develop strategies for achieving SDGs. The strategy for achieving SDGs indicator targets is based on factors found in Bone Bolango Regency, sorted based on a priority scale, namely regulatory support, RPJMD priorities, institutional support, budget support and partnerships.